2010
DOI: 10.1002/mawe.201000646
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of sulphur‐alloyed spray‐formed steels

Abstract: Small amounts of sulphur improve cutting properties of conventionally produced steels. In combination with manganese, sulphur forms manganese sulphide inclusions in the steel matrix which reduce the tool wear during machining and improve machinability. However, manganese sulphides may have a detrimental effect on the mechanical properties. Hot forming operations result in an elongation of sulphides in rolling direction and may decrease the fatigue properties under stresses in the transverse direction. In compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Besides, Tinscher et al revealed that the homogeneous and isotropic microstructure of spray formed bearing steel resulted in an isotropic mechanical properties including high fatigue resistance perpendicular to the rolling direction. Schumacher et al attempted to increase the amount of sulfur element of the bearing steel by spray forming in order to improve the machinability without reducing fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Tinscher et al revealed that the homogeneous and isotropic microstructure of spray formed bearing steel resulted in an isotropic mechanical properties including high fatigue resistance perpendicular to the rolling direction. Schumacher et al attempted to increase the amount of sulfur element of the bearing steel by spray forming in order to improve the machinability without reducing fatigue strength.…”
Section: Introductionmentioning
confidence: 99%